The Relationship Of Clean Water And Environmental Sanitation To The Incident Of Diarrhea: Systematic Review - Rahmadani Siregar, Dewi; Razak, Abdul; Yuniarti, Elsa; Handayuni, Linda (Sam Ratulangi University, 2024)
Indonesia is one of the developing countries that experiences diarrhea problems. This is because of its high morbidity and mortality. Diarrhea is an endemic disease that has the potential to cause Extraordinary Events (KLB) which are often accompanied by death in Indonesia. Most diarrheal diseases can be prevented through safe drinking water and adequate sanitation and hygiene. This study aims to determine the relationship between environmental sanitation and the incidence of diarrhea in toddlers. This research uses a systematic review method (Systematic Review) which is a research method for identifying, evaluating, and interpreting research results that are relevant to a particular research topic, or phenomenon that is the focus of the research. The results of this research show that there is a relationship between environmental sanitation such as the physical quality of water, ownership of a toilet, type of floor in the house, and the incidence of diarrhea. It is hoped that after this research is carried out, mothers and health policy stakeholders such as the health department and community health centers can improve residential environmental health programs to have physically clean water quality and good environmental sanitation. Keywords: Environmental Sanitation, Diarrhea, Toddlers, Systematic Review